An Appraisal of Emergent Post Covid-19 Challenges and Preventive Strategies in Nigeria Primary Schools - Oladejo, Bolaji (Ilorin Journal of Education, 2022)
The impacts of Covid-19 cut across every sector around the world. While many have taken interest in investigating the challenges and impacts of Covid-19 on a larger and major scopes, this paper is an appraisal of the emergent post Covid-19 challenges and preventive measures in primary schools in Nigeria. The paper reviews the changing methods and responsibilities of teachers and other stakeholders during post covid-19 period in primary schools in Nigeria. The paper appraises the challenges associated with post Covid-19 preventive measures in primary schools such as little understanding of the effective use of facemasks by primary school pupils, anxiety and loss of manpower. This paper also proposes better preventive strategies such as the use of face masks, hand sanitizer, placing of hand washing water at strategic places in school environment, distance seating arrangement, coughing, sneezing to the elbow, temperature screening equipment and their effects on health, psychosocial, interpersonal relationship and anxiety among school stakeholders.